Emirati Novel between Origins and Development - Almatrooshi, Rasha; Bouali, Abderrahmane; Al-Abidi, Laila (Al-Adab Journal, 2024)
This research seeks to present research on the modern Emirati novel, whose emergence within the framework of modern Arabic literature was a distinct event, after the entire Arab Gulf region witnessed a wide literary renaissance in culture and development. The aim of this research was to illuminate this cultural and literary space. We opened our research with an introduction. In the introduction, we discussed the subject, the reason for choosing it, and the approach followed. We presented a definition of the novel as a literary genre that came to us from the West after the Napoleon campaign, that campaign that initially affected Egypt, then the influences moved to the Arab world. After that, we divided the research into tow axes: The first axis we devoted to the topic of the emergence of the Emirati novel, its development, and its trends: the historical, social and feminist trend ... and we separated some of its problems and issues. As for the second axis, we discussed the subject of the technical elements of the Emirati novel. In it, we talked about the event, personality, time, place and language, all of which are essential elements in the art of the novel.